Sport tourism development - Kalacas, Maria Rellie B.
"Tourism is an important sector for economic development in a country. With a year ahead full of important sporting events, we look at how sports tourism has grown in importance from niche market to multi-billion dollar business. Sport and tourism each contribute a great deal to the global economy and have become an element in the armoury of politicians, planners and economists seeking to regenerate local economies. The trend to increase sport touristic experiences and to provide them in faraway, often very different cultures simply increases the importance of addressing both the potential positive and the negative sociocultural impacts of sport tourism. This book critically explores sport-related tourism drawing on the fields of sport management, sports marketing, economic, sports geography, and tourism studies." --